Virtual Reality Mobile Application Development with Scrum Framework as a New Media in Learning English - Chandra, Albert Yakobus; Prasetyaningrum, Putri Taqwa; Suria, Ozzi; Santosa, Paulus Insap; Nugroho, Lukito Edi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Virtual reality is a combination of technology that are used to visualize and provide interaction with virtual environment. These environment often depict three-dimensional space which could be realistic or imaginary. One of the problem to build a virtual reality application is not yet available an approach as development lifecycle to build this virtual reality application. In this study we implement a software development project management approach which is Scrum to build a virtual reality application to be a new media for learning English. The goal is to find out how this system development approach is providing a new guide as a project management to build virtual reality application right from the project started, until the application is reach production stage or final release. Also in this study we using the unity 3D to create the virtual environment and C# as the backend programming language to build a mobile application which is made this virtual application is build using cross platform mobile development. The study concludes that mobile learning applications increase student motivation and place students as the main subject in English Lessons to support the teaching and learning process in an educational context.